What happens after psychiatric diagnosis? The course and type of intervention at Landspitali - The National University Hospital of Iceland - Inga Guðlaug Helgadóttir 1984- (2018)
Background: The aim of this study is to analyse what happens to patients after being diagnosed with psychiatric illness, with regards to the course and type of intervention they received in the mental healthcare service in Iceland. Objective: To investigate whether or not diagnostic procedures in Landsspitali - The National University Hospital in Iceland are conducted in accordance with clinical guidelines and to map continuity of treatment, collaborative care and efficiency between interdisciplinary professionals and also between different mental health units. Participants: The participants were 191 patients receiving treatment for mental health problems at an outpatient unit at Landspítali between 2010 and 2012. Methods: The study is based on data from patient‟s medical history database. Checklist was used to gather information. Results: The results suggest that the use of standardised diagnostic interviews is an exception rather than a rule. There is also a difference between healthcare professionals in use of standardised diagnostic interviews (SDI) (like assessment guidelines advise), psychologist being most likely to use it and psychiatrists the least likely. In 80% of cases, were patient received two or more diagnosis; the diagnosis either changed to different diagnosis or was unstable throughout the period. Those who receive a psychiatric diagnosis based on SDI receive significantly more diagnoses throughout the process. Furthermore, significant correlation is between numbers of received diagnoses and number of arrivals at the psychiatric ward. Conclusion: Evidence based assessment is fundamental for an accurate diagnosis. It may reduce the likelihood of an unstable diagnosis and maximise the likelihood that treatment will be effective. Key Words: Psychiatric diagnosis, course of interventions, standardized diagnostic interviews, clinical guidelines.